PLGA-based biocompatible nanoparticles improved anti-breast tumor efficacy of 1,25(OH)2D3 through the SOCS3/STAT3/EMT signaling axis - JinJing Pan; Ping Wang; Linghong Xiong; Wenqing Yang; Jie Li; Kai Yang; Bingyan Li (Journal of Functional Foods)
Several studies have demonstrated that active vitamin D (1,25(OH)2D3) can impede the cancerous traits of breast cancer. However, due to the susceptibility of 1,25(OH)2D3 to degradation in the tumor microenvironment, higher doses were required to sustain its efficacy. This elevated dosage could lead to significant side effects, thereby constraining its practical application in clinical settings. The FDA-approved nanomaterial poly (lactic-co-glycolic acid) (PLGA) had the potential for utilization in clinical settings. It could be employed to helps in maintaining and extending the biological activity of the drugs, thereby enhancing their therapeutic efficacy. Hence, the potential of PLGA encapsulation to augment the anti-breast cancer properties of 1,25(OH)2D3 and the underlying mechanism remain uncertain. In this study, our findings not only demonstrated the effective encapsulation of 1,25(OH)2D3 in PLGA (PLGA-1,25(OH)2D3, PD) but also indicated that the PD has a more potent inhibitory effect on the proliferation and migration of breast cancer cells compared with 1,25(OH)2D3 alone. Consistently, PD exhibits superior efficacy in suppressing subcutaneous neoplasia and lung metastasis of breast cancer cells compared to 1,25(OH)2D3. It is noteworthy that PD significantly alleviates the adverse effects of increased serum calcium levels and weight loss in mice induced by 1,25(OH)2D3. Subsequently, bioinformatics analysis and western blot confirmed that PD showed a more pronounced upregulation of SOCS3 and a concurrent downregulation of JAK/STAT3 and PI3K/AKT signals compared to 1,25(OH)2D3 both in vivo and in vitro. Considering that epithelial-mesenchymal transition (EMT) is downstream of the SOCS3/STAT3/PI3K pathway, our findings also revealed that 1,25(OH)2D3 markedly regulated the expression of EMT markers. Additionally, the inhibitor of STAT3 exhibited inhibitory effects on EMT progression in breast cancer cells. Moreover, we manifested that PD robustly curtailed the EMT markers compared to 1,25(OH)2D3 in vivo. In conclusion, these findings elucidate PLGA-1,25(OH)2D3 enhances 1,25(OH)2D3's antitumor effects through the SOCS3/STAT3/EMT signaling axis, offering potential targets for therapeutic interventions in breast cancer treatment.